Ibn Khaldoon’s Historical Judgments (d. 808A.H/1406 C.E) An Analytical Study - Abed Al-janabi, Saad Kadhom (Opción, 2019)
This study focused on the historical judgments that Ibn Khaldun included in his historical works, about personalities and events, whether in his era or in pre-era times, and these provisions were characterized by the inevitable judgments came as a result of the conviction of Ibn Khaldun, including his writings so that all his novels are based on a curriculum Critical and clear, in order to reach a final historical judgment, which made its historical material significantly different from other historians, both those who preceded them or contemporaries of it.